Public space, public discourse, and public libraries - Alstad, Colleen (2021)
The traditional mission of the public library—supporting the self-education of the citizenry in order that they may become fully participating members in a democratic society—has been devalued of late in favour of popularizing the library to attract more users. This shift has led to an emphasis on entertainment and marketing, and an abandonment of what many feel is the true purpose of a library. Loss of democratic tradition has simultaneously occurred on another front: civic space which allows for public assembly and discourse has disappeared or been downgraded into places for leisure and recreation rather than politics, with a concomitant decline in the quality of public discourse as citizens increasingly depend on profit-driven mass media for their “opinions.” This paper contends that the public library is an ideal physical and psychological space for public discourse. By supporting public discourse, the public library can begin to reinvigorate both the quality of public discourse and its traditional commitment to democratic ideals.